Investigation of residual stress retention of titanium alloy after different levels of material removal - Muhammad Siddiq Bin Abdul Shukor (Nanyang Technological University, 2024)
Compressive residual stresses within a material are beneficial. It provides benefits such as increasing fatigue strength and fatigue life, it is also able to inhibit crack propagation and it is due to these benefits that they are widely utilized in industries such as the aerospace industry. Compressive residual stress may be induced into the material via plastic deformation of the surface of the material. The impact of the processes will then propagate into the material thus altering the microstructure within the material. To induce them, industries commonly utilize processes such as deep cold rolling and hammer peening, which involves plastically deforming the surface of the material. However depending on the parameters set on these processes, compressive residual stresses are not able to propagate all the way through the material, there will be a point whereby the strength of the compressive residual stresses will decreases as the depth of analysis increases, hence the goal of this study is to identify as to where this will occur, effectively this study focuses on the degree of compressive residual stress retention of Ti64 which is the primary material of this study. Specimens of hammer peened Ti64 were used, each specimen have also undergone different levels of material removal at that the location whereby the hammer peening was conducted. Despite the differing levels of material removal among the specimens, compiled their residual stress analysis exhibited a trend which coincided with residual stress analysis conducted on a hammer peened specimen of Ti64 that was not subjected to material removal.